TANGGAP PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS KEDELAI (Glycine max L.) TERHADAP PERBANDINGAN KOMPOSISI PUPUK - Teguh Satwiko; Ratna Rosanty Lahay; B. Sengli J. Damanik (Jurnal Agroekoteknologi, 2013)
The use of organic fertilizer is needed to replace the role of chemical fertilizers, preserving theenvironment and for sustainable agriculture. The study was conducted in Tanjung Sari, KecamatanMedan Selayang. The research used a Randomized Block Design with two factors. The first factoris varieties (Argomulyo, Burangrang and Anjasmoro). The second factor is the ratio of chemicalfertilizers and vermicompost, which include : chemical fertilizer 0% + vermicompost 100%,chemical fertilizer 25% + vermicompost 75%, chemical fertilizer 50% + vermicompost 50%,chemical fertilizer 25% + vermicompost 75%, and chemical 100% + vermicompost 0%. The resultshowed that Varieties significantly affected the parameters amount of produtive branch, weight ofdry plant, weight of dry root, the number of pods per plant, the number of filled pods per plant,weight of dry seed per sample,and weight of 100 seeds. Varieties did not significantly affect theparameters weight of dry seed per plot. The composition ratio of fertilizers significantly affectedthe parameters weight of dry root, weight of dry seed per sample,and weight of 100 seeds. Inaddition, the ratio of chemical fertilizers and vermicompost did not significantly affect theparameters amount of produtive branch, weight of dry plant, the number of pods per plant, thenumber of filled pods per plant,and weight of dry seed per plot. The interaction between varietiesand the ratio of chemical fertilizers and vermicompost did not significantly affected for allparameters.Key words : varieties, chemical fertilizers, vermicompost, soybeanABSTRAK